Altered erythroid‐related miRNA levels as a possible novel biomarker for detection of autologous blood transfusion misuse in sport. Issue 8 (30th May 2019) - Gasparello, Jessica; Lamberti, Nicola; Papi, Chiara; Lampronti, Ilaria; Cosenza, Lucia Carmela; Fabbri, Enrica; Bianchi, Nicoletta; Zambon, Christel; Dalla Corte, Francesca; Govoni, Maurizio; Reverberi, Roberto; Manfredini, Fabio; et al.
Abstract : BACKGROUND: Autologous blood transfusion (ABT) is a performance‐enhancing method prohibited in sport; its detection is a key issue in the field of anti‐doping. Among novel markers enabling ABT detection, microRNAs (miRNAs) might be considered a promising analytical tool. STUDY DESIGN AND METHODS: We studied the changes of erythroid‐related microRNAs following ABT, to identify novel biomarkers. Fifteen healthy trained males were studied from a population of 24 subjects, enrolled and randomized into a Transfusion (T) and a Control (C) group. Seriated blood samples were obtained in the T group before and after the two ABT procedures (withdrawal, with blood refrigerated or cryopreserved, and reinfusion), and in the C group at the same time points. Traditional hematological parameters were assessed. Samples were tested by microarray analysis of a pre‐identified set of erythroid‐related miRNAs. RESULTS: Hematological parameters showed moderate changes only in the T group, particularly following blood withdrawal. Among erythroid‐related miRNAs tested, following ABT a pool of 7 miRNAs associated with fetal hemoglobin and regulating transcriptional repressors of gamma‐globin gene was found stable in C and differently expressed in three out of six T subjects in the completed phase of ABT, independently from blood conservation. Particularly, two or more erythropoiesis‐related miRNAs within the shortlist constituted of miR‐126‐3p, miR‐144‐3p, miR‐191‐3p, miR‐197‐3p, miR‐486‐3p, miR‐486‐5p, and miR‐92a‐3p were significantly upregulated in T subjects after reinfusion, with a person‐to‐person variability but with congruent changes. CONCLUSIONS: This study describes a signature of potential interest for ABT detection in sports, based on the analysis of miRNAs associated with erythroid features.